Neonatal Resuscitation Research Priorities in Low- and Middle-Income Countries - Vivek V. Shukla; Somashekhar M. Nimbalkar (Hindawi Limited, 2021)
Several critical physiological changes occur during birth. Optimal and timely resuscitation is essential to avoid morbidity and mortality. The International Liaison Committee on Resuscitation (ILCOR) is a multinational committee that publishes evidence-based consensus and treatment recommendations for resuscitation in various scenarios including that for neonatal resuscitation. The majority of perinatal deaths occur in low- and middle-income countries (LMICs); however, there is limited research output from LMICs to generate evidence-based practice recommendations specific for LMICs. The current review identifies key areas of neonatal resuscitation-related research needed from LMICs to inform evidence-based resuscitation of neonates in LMICs.